Research infrastructure in Slovenia and the role of academic libraries (Libellarium: journal for research in the field of information and related sciences, 2016)
In Slovenia, the scientific research infrastructure is implemented through a variety of information systems, and through other many times integrated systems. Due to the development of information and communication technologies, academic libraries are able to create, develop and maintain new library and information services by using the research infrastructure, which has not been used before. Some of these infrastructure systems in which the Central Technological Library at the University of Ljubljana participates are described in this paper. The paper discusses the activities of the Central specialized information centres as part of the Slovenian Current Research Information System SICRIS, consortial procurement of international scientific literature, and library's participation in some of the research projects. A new niche for the affirmation of academic libraries, special information services, such as the information support to the researchers in the process of publication in open access, are also discussed.
Keywords: research infrastructure; Slovenia; academic libraries